In a split second: Handwriting pauses in typical and struggling writers - Pascual, Mariona; Soler, Olga; Salas, Naymé (Frontiers in Psychology, 2023)
The same two-second threshold has frequently been used when analyzing the writing processes of different types of writers across various writing tasks (Alamargot et al., 2010; Alves et al., 2007; Connelly et al., 2012). Because immature writers are constrained by transcription processes during writing (Berninger et al., 1992; Limpo et al., 2017), we focused on identifying the average pause duration for handwriting execution pauses, which have been mostly overlooked before. The present study aimed to provide an evidence-based account of the average number and duration of handwriting pauses to observe any developmental trends (3rd and 5th graders) and to identify process-level markers of writing difficulties (typically-developing v. struggling writers). We examined pauses by controlling for several letter features in a handwriting-only task to isolate pauses that could only be attributed to handwriting processes. Our results with 3rd and 5th graders with and without writing difficulties showed that the average pause duration is of 400 ms, in line with the short duration of pauses previously attributed to this process (Alves et al., 2007; Prunty et al., 2014; Wengelin, 2007). In a cross-classified multilevel model analysis, we found that within-letter pause duration was not conditioned by letter features, but pause number was conditioned by the strokes of the letter and the script in which the letters were written. Moreover, the handwriting fluency score (in which Grade and Group are embedded) was the main factor to condition both pause number and duration, where both the younger and the struggling writers had more and longer pauses. We discuss the theoretical and educational implications of our findings and provide recommendations for thresholds in the analysis of pauses in writing development research.